Professional satisfaction among emigrated Nurses of Nepal: A cross-sectional web-based study - Kshitij Karki; Devendra Raj Singh; Sushmita K.C; Sanjeev Kumar Shah; Nanda Singh Shrestha (Al Ameen Medical College, 2020)
Background: Professional satisfaction is nowadays leading cause in increasing emigration of Nurses of Nepal. Thus, this research was conducted to identify the level of professional satisfaction among emigrated nurses in Nepal. Methods: A cross-sectional descriptive study was conducted among 102 emigrated Nepalese Nurses staying in the USA, UK, UAE, Australia, Denmark and Canada. A web-based semi-structured questionnaire based on the McCloskey/ Mueller Satisfaction Scale was used to collect data from participants. Data were analysed using statistical package for social science (SPSS) version 24. The descriptive and inferential statistical analysis was conducted to interpret the data. Results: The participants for the study were from Australia (57.8%) followed by USA (25.5%), UK (10.8%), from Canada (2.9%), UAE (2%) and Denmark (1%). It was found that 74.5% of participants were from 25-30 years of age group. The emigrated Nurses working in Australia were highly satisfied (74.6%) with their job. This study showed that the majority (68.63%) of participants had a high satisfaction level in their job abroad where 2.9% had a lower satisfaction level. Conclusion: It is concluded that Nepalese nurses have a high professional satisfaction level working in abroad. So, the government needs to plan the retention of nurses in the countries considering the facilities and motivation provided in the emigrant countries.